2018
DOI: 10.1177/0033294118781855
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Coping and Emotion Regulation in the Occurrence of Suicidal Behavior

Abstract: Research has shown that the use of maladaptive coping strategies and difficulties in regulating mood are linked to increasing risk of suicide. This study measured the impact of coping and emotion regulation on suicidal behavior in a sample of Asian students. The aim was to determine whether different coping strategies and methods of expressive suppression and cognitive reappraisal would be associated with suicidal behavior. One hundred and twenty undergraduate students were recruited from The Open University i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 66 publications
6
50
1
5
Order By: Relevance
“…Accordingly, previous studies have found negative associations between maladaptive strategies (e.g., rumination, self-blaming, etc.) and depressive symptomatology and suicide risk [ 29 ]. In contrast, adaptive strategies were negatively associated with suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, previous studies have found negative associations between maladaptive strategies (e.g., rumination, self-blaming, etc.) and depressive symptomatology and suicide risk [ 29 ]. In contrast, adaptive strategies were negatively associated with suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Extremera et al [ 19 ] have found recently that some adaptive cognitive emotion regulation strategies act as mediators in the associations between EI and well-being. At the same time, accumulating evidence suggests that the use of maladaptive coping strategies, the limited access to effective emotion regulation strategies and difficulties in regulating emotions are related to an increased risk of suicidal ideation [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance effectiveness of psychological interventions, the ESQ addresses the need to mechanistically target factors which are both causally associated with poor mental health and modifiable by an intervention. Poorer coping strategy and emotional dysregulation are the powerful predictors of threatening behaviours and suicidal ideation (Ong & Thompson, 2019). Understanding how individuals adapt to threats to well-being may provide new insight about the common targeted mechanisms of well-being.…”
Section: Future Implicationsmentioning
confidence: 99%
“…Those who used maladaptive skills had significantly higher mean ranks for scores on anxiety symptoms, depressive symptoms, and PSQI. Adaptive coping skills are more effective in dealing with difficult situations and in managing negative emotions than maladaptive skills [ 45 ]. It is of paramount importance to understand the effective, individualized ways of coping in a situation like this pandemic [ 46 ].…”
Section: Discussionmentioning
confidence: 99%